ANALYSING THE SECTORS AND COUNTRIES OF ORIGIN FOR THE TOP RANKING BRANDS. ARE THERE ANY COMMON PATTERNS? - Erika KULCSÁR; Kinga SZŐCS (Management & Marketing)
It is a well-known fact that brands play an increasingly important role in our lives. The branding process becomes a reality for even those who strictly separate themselves from the world of brands: there is no longer any sector where brands would not have penetrated into. It is also well-known that not all brands are characterized by long-term success, not even the international ones. However, there are brands so deeply embedded in cultural globalization that almost every nation regards them as their own. We have to admit that not all brands succeed to do so. Interbrand is the organization that selects and publishes the most valuable brands in the world every year. How has the top ranking of the brands evolved over the years, which brands have failed, which are the newcomers? Or which brands can successfully respond to the environmental changes – no matter if these are macro or micro changes - and fundamentally determine the demand for each sector – are among our top concerns in our research.